An assessment of workplace conflict management in Zimbabwean local authorities. a case of Masvingo City Council - Jaravaza, Alice (Midlands State University, 2020)
Zimbabwean Urban Local Authorities are established in terms of the Urban Councils Act Chapter 29:15 Section 4 (1) (a – d). The Central government formed urban councils as the government that is closer to the people at grass roots level in which these local bodies have been delegated both legislative and fiscal authority. Urban Local authorities are a diverse community where different people from all walks of life acquire different types of services and goods. They follow rules and procedures that govern them on their day to day business. In addition there is day to day interaction of people with diverse perspectives, behavior, attitudes among other differences that cause workplace conflict unavoidable. The purpose of this research is to assess the management of workplace conflict at Masvingo City Council, looking at the background of the study, statement of the problem in the management of workplace place at Masvingo City Council, objectives of the study, research questions, significance of the study, literature review, research methodology and other subtopics that the researcher is going to cover.